Enhancing teaching materials development course with the ICARE learning model in e-learning - Simamora, Alexander Hamonangan; Agustini, Ketut; Sudatha, I Gde Wawan; Suartama, I Kadek (Journal of Education and Learning (EduLearn), 2024)
Using e-learning in higher education has many important benefits and advantages in todays world of education. Therefore, this research aims to develop e-learning based on the introduction, connection, application, reflection, extend (ICARE) learning model for developing teaching materials courses in the Faculty of Education, Universitas Pendidikan Ganesha. The Hannafin and Peck development model was adopted as a foundational method, and the digital content developed was subjected to formative evaluation methods, including i) expert validation, ii) individual assessment, and iii) small group evaluation. To ascertain the quality of the developed content, the research engaged 3 expert evaluators, each specializing in media, instructional design, and content. Concurrently, individual evaluation was carried out with 3 students, followed by a small group evaluation involving 9 additional students. Data collection techniques involved both observational measures and questionnaire-based inquiries. The expert assessment showed that the design, media, and content dimensions all fell within the "very good" category. Student reactions, as measured through both individual and small group evaluations, consistently aligned with the "very good" category. Therefore, the attractiveness and practicality of electronic learning (e-learning) fell under the "very good" classification, due to the implementation of the ICARE learning model as the foundational design principle.